Pediatric residents’ and attending physicians’ perspectives on the ethical challenges of end of life care in children - Ebrahimi, Alireza (J Med Ethics Hist Med, 2018)
One issue that has received less attention in present health care protocols is pediatric palliative care (PPC), which is an approach to care starting with the diagnosis of life-threatening diseases in children. It embraces physical, emotional and spiritual elements. Ethical issues are major concerns in today’s pediatric health care guidelines and must be considered by residents and attending physicians in this field. The present study was conducted in Namazi Teaching Hospital, Shiraz, Iran. Forty-eight out of 92 pediatricians were enrolled in this research, including 8 attendings, 6 fellows, and 34 residents. The study questionnaire consisted of 66 items. It was built based on previous reliable and validated questionnaire; also the calculated Cranach’s alpha was 0.815. Data were analyzed and presented by mean SD and percentage. While seventy-five percent of the participants reported involvement in pediatric palliative care, fifty-six percent did not acknowledge any information about the subject. More than half of the participants perceived the pediatric palliative care services in Namazi Hospital as somewhat or completely satisfactory. Furthermore, thirty-five percent of the applicants stated that they encounter an ethical problem with regard to PPC once a week. There are many challenges to providing decent palliative care for children, including symptom controlling, shifting to end of life care, background dissimilarities of patients, financial restrictions, and acceptance of death. Our applicants believed that offering psycho-spiritual support was the most important challenge in PPC. However, further investigations are needed to determine other requirements for providing a comprehensive guideline on PPC.